(untitled) (European Bison Conservation Newsletter, 2008)
After the extirpation of last population of the European bison Bison bonasus (L.) at Białowieska Forest (1919) and in Caucasus (1926 or 27), under the framework of the International Society for European Bison Protection in Germany, the restitution of the species was initiated, on the basis of individuals surviving in captivity. In 1924 Groeben recorded 66 (33,33) living individuals, and in a pedigree record from 1931 given are genealogical data of 171 animals, including 65 still alive, which became a potential founder herd for contemporary bison. European Bison Pedigree Book (EBPB) for the period 1931 – 1936 (Goerd v.d. Groeben, Erna Mohr) was edited in Germany, and after a break, since 1947 in Poland (Jan Żabiński). Since 1991, the editorial office is situated at Białowiez˙a, within the structure of Białowieski National Park. EBPB, thanks to co-operation with owners of animals, is maintaining a continuous pedigree registration of pure blood European bison in breeding enclosures, and is monitoring bison numbers in free ranging herds. Data, published annually are available for animals’ owners, and for other interested parties. In 2005, the world population of European bison was estimated for 3439, out of which 62% were living at freedom.